Kaji Banding Kualitas Semen Segar Empat Genetik Ayam Lokal Indonesia (COMPARATIVE STUDY ON THE QUALITY OF FRESH SEMEN OF FOUR GENETIC LOCAL CHICKEN IN INDONESIA) - Junaedi, Junaedi; Husnaeni, Husnaeni (Jurnal Veteriner; Vol 20 No 3 (2019), 2019)
This study was conducted to examine the comparison the quality of spermatozoa in four genetic groups of poultry (Pelung chicken, Nunukan chicken, Sentul chicken, and Bangkok chicken). The parameters of this study were the concentration of spermatozoa, motility, viability, semen volume, color, and consistency. The study was designed using a Completely Randomized Design (CRD) with four local chicken nations and four replications. The results showed that the volume of Nunukan chicken semen was 0.32±0.01 mL/ejaculation, Bangkok chicken was 0.31±0.01 mL/ejaculate, Sentul chicken was 0.15±0.02 mL/ejaculate and Pelung chicken was 0.23±0.02 mL/ejaculation. the color of fresh semen is white (Pelung chicken, Nunukan chicken and Sentul chicken) except chicken Bangkok has the color of cream semen. Pelung chicken has a concentration of spermatozoa 5,043.33±51 million/mL, Nunukan chicken 3,250.22 ±45 million/mL, Sentul chicken 3,002.87±67 million/mL, and Bangkok chicken 3,002.87 ± 67 million/mL. Motility of Pelung chicken 84.,69 ± 1.12%, Bangkok chicken 82.35±1.85%, Nunukan chicken 77.74±1.57% and Sentul chicken 77.64±1.65%. Viability spermatozoa of Sentul chicken was 90.35 ± 1.21%, Bangkok chicken was 90.64 ± 1.16%, Pelung chicken was 89.17 ± 1.23% and Nunukan chicken was 86.29 ± 1.15%. It can be concluded that the motility spermatozoa of Pelung chicken and Bangkok chicken is better than the spermatozoa motility of Nunukan chicken and Sentul chicken. The viability of Sentul chicken and Bangkok chicken was higher compared to the viability semen of chicken Pelung and chicken Nunukan.